Effect of excessive gestational weight gain before and after 28 weeks on trial of labor after cesarean stratified by pre-pregnancy body mass index: a retrospective cohort study - Liu, Guangpu; Zhang, Jingya; Zhou, Chaofan; Zhang, Huixin; Shen, Haoran (Frontiers in Medicine, 2023)
This study aimed to assess the effect of excessive gestational weight gain (GWG) before and after 28 weeks on the mode of delivery in women who attempted a trial of labor after cesarean (TOLAC), stratified by pre-pregnancy BMI. A retrospective analysis of the outcomes of eligible women who attempted trial of labor after cesarean (TOLAC) in a Chinese hospital from January 2016 to October 2022 was performed. GWG before and after 28 weeks was categorized as ‘excessive’ or ‘non-excessive’ based on the guideline of Institute of Medicine (IOM). Multivariable logistic regression analyses were used to estimate the effect of excessive GWG before and after 28 weeks on mode of delivery in women who underwent TOLAC, stratified by pre-pregnancy BMI. Of the 512 women who underwent term trial of labor, 71.1% achieved a vaginal birth. No correlation was found between excessive GWG before 28 weeks and the rate of vaginal birth after cesarean (VBAC). Among women with or without excessive GWG before 28 weeks, excessive GWG after 28 weeks was significantly associated with a reduced rate of VBAC. When stratified by pre-pregnancy BMI, women who had excessive gestational weight gain after 28 weeks gestation had lower rates of VBAC than those who did not, regardless of being underweight, normal or overweight (aOR 0.23, 95% CI 0.06–0.88; aOR 0.42, 95% CI 0.25, 0.70; and aOR 0.12, 95% CI 0.04–0.36; respectively). Excessive weight gain after 28 weeks of pregnancy was related to decreased rates of VBAC, irrespective of pre-pregnancy weight status and weight gain before 28 weeks.